Radar probing of surfactant films on the water surface using dual co-polarized SAR - S.A. Ermakov (2016)
Microwave radar is a very perspective tool for all-weather monitoring of film slicks which appear in radar imagery of the water surface as areas of reduced backscattering due to damping of short wind waves. Information about the backscatter variations obtained from single band/one polarization radar seems to be insufficient for film characterization, so, new capabilities of multi-polarization radar for monitoring of film slicks have been actively discussed in the literature. In this paper results of new field experiments on remote sensing of film slicks using dual co-polarized radars: a satellite X-band TerraSAR-X and recently designed at IAP RAS a Multifrequency Radar Complex - three-band scatterometer operating in X-/C-/S-bands and mounted onboard a ship are presented. Along with backscattering depression the variations of polarized (Bragg) and non polarized radar backscatter components in slicks were analyzed. It is obtained that VV-to-HH backscatter ratio is smaller than the ratio predicted by a Bragg (two-scale) model thus indicating that additional, non polarized (NP), component also contributes to the total radar backscatter. Assuming the radar backscatter to be a sum of polarized (Bragg) and NP components the latter was eliminated from the total radar backscatter, and contrasts for the Bragg and NP components were obtained. The contrasts for the polarized component allowed us to estimate damping of gravity-capillary wind waves at Bragg wavelengths in slick and to give more accurate comparison with models of wave damping due to elastic film.